2008
DOI: 10.1186/1471-2156-9-52
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in a member of the laminin gene family affects variation in body composition in Drosophila and humans

Abstract: Background: The objective of the present study was to map candidate loci influencing naturally occurring variation in triacylglycerol (TAG) storage using quantitative complementation procedures in Drosophila melanogaster. Based on our results from Drosophila, we performed a human population-based association study to investigate the effect of natural variation in LAMA5 gene on body composition in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
4
16
2
Order By: Relevance
“…The association of rs659822 with body weight and lean tissue mass was also observed in African-American women from the same population (De Luca et al, 2008); however, the effect of rs659822 on these traits in the African-American women had opposite direction, which suggests its context dependence with respect to other genes and/or environmental factors. In the same study, LAMA5 rs659822 was also associated with HDL-cholesterol (HDL-C) levels in the Caucasian women (De Luca et al, 2008). …”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…The association of rs659822 with body weight and lean tissue mass was also observed in African-American women from the same population (De Luca et al, 2008); however, the effect of rs659822 on these traits in the African-American women had opposite direction, which suggests its context dependence with respect to other genes and/or environmental factors. In the same study, LAMA5 rs659822 was also associated with HDL-cholesterol (HDL-C) levels in the Caucasian women (De Luca et al, 2008). …”
Section: Introductionmentioning
confidence: 76%
“…By performing quantitative genetic studies in the fruit fly Drosophila melanogaster and a population-based study in a human cohort, De Luca et al (De Luca et al, 2008) recently identified LAMA5 as a potential candidate gene influencing body composition traits. They showed that Caucasian premenopausal women who were homozygous for the less frequent C-allele of the LAMA5 rs659822 polymorphism had shorter stature and lower body weight, total fat mass, and lean tissue mass than those carrying at least one T allele (De Luca et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other genes identified regulate fatty acid metabolism, the citric acid cycle, oxidative phosphorylation, and apoptosis. These specific genes have been shown to be involved in some manner with obesity or body weight regulation [38,39].…”
Section: Mechanisms Implicated In Weight Regainmentioning
confidence: 99%